(untitled) (Annals of Medical Research, 2021)
Aim: The appropriate anesthetic technique to be used in cases of proximal hypospadias in children is a subject of debate. Local or regional anesthesia as well as intubation can be used. In this study, it was aimed to evaluate retrospectively the different anesthesia and surgery techniques used and their perioperative outcomes in the cases of proximal hypospadias consulting our hospital.Materials and Methods: The hospital files of 30 cases operated on for proximal hypospadias were scanned retrospectively to evaluate the different methods of anesthesia and repair surgery implemented. The patients operated under general anesthesia were grouped on the basis of the airway equipment used for anesthesia as Laryngeal mask airway (Group 1) and endotracheal intubation (Group 2). Routine penile block implementation, effectiveness of anesthesia, side effects, hemodynamic changes and complications in all patients were recorded. Results: A total of 56 sessions of operations on 28 patients were carried out. In 26 of the session’s laryngeal mask and in 30 sessions endotracheal intubation were used. When the data of Group 1 and Group 2 were compared, the groups did not differ significantly with respect to age, anesthesia methods and duration, hypospadias repair methods, duration and sessions, intraoperative parameters, hospital stay and complications (all p>0.05). The two groups differed on the ASA physical status classification values with Group 2 values being significantly higher (p0.05).Conclusion: Effectiveness of anesthesia by using LMA or endotracheal intubation were perioperatively equivalent during repair of proximal hypospadias with different methods of surgery.